2021
DOI: 10.1021/acs.langmuir.1c02222
|View full text |Cite
|
Sign up to set email alerts
|

Multimotion of Marangoni Propulsion Ships Controlled by Two-Wavelength Near-Infrared Light

Abstract: Multimode motion of Marangoni propulsion ships on a water surface as per a near-infrared, two-wavelength selective response is achieved for the first time. The ships are rhombus-or propellershaped polyacrylamide or siloxane resin-based gels in which Nd 2 O 3 and Yb 2 O 3 nanoparticles are incorporated separately for photothermal conversion at 808 and 980 nm, respectively. The rhombus geometry is for straight locomotion, and the propeller geometry is for rotation. On/off remote control of the forward and backwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Among them, photothermal conversion technology is the most direct application of solar energy. Photothermal conversion materials which can directly convert absorbed light energy into thermal energy have been widely used in photothermal energy storage, , photothermal deicing, , seawater desalination, , and light-driven. , These materials usually include metallic materials, , carbonaceous materials, and conducting polymers . However, photothermal conversion materials face serious rainwater corrosion and environmental pollutant pollution problems during long-term outdoor operation, which significantly affects their performance stability and service life.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, photothermal conversion technology is the most direct application of solar energy. Photothermal conversion materials which can directly convert absorbed light energy into thermal energy have been widely used in photothermal energy storage, , photothermal deicing, , seawater desalination, , and light-driven. , These materials usually include metallic materials, , carbonaceous materials, and conducting polymers . However, photothermal conversion materials face serious rainwater corrosion and environmental pollutant pollution problems during long-term outdoor operation, which significantly affects their performance stability and service life.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of a multi-component photothermal layer is often complex and difficult to scale up. [15,25] It is desirable to develop single-component photothermal materials to achieve easy and large-scale fabrications. To derive a single-component photothermal material with a catechol-Fe 3+ crosslinked polymer, we synthesized a copolymer MMA/BA/Eug-OH (MMA = methyl methacrylate; BA = butyl acrylate; Eug-OH = 1,2-Dihydroxy-4-allylbenzene) with the catechol group hanging from the side chain.…”
Section: Materials Synthesis and Characterizationmentioning
confidence: 99%
“…21 However, a majority of the photoresponsive hydrogel actuators reported to date respond to near-infrared wavelengths, with only a few in the visible range, 16 thus limiting the possibilities for multiwavelength actuation. 22,23 In this regard, gold nanoparticles are great candidates as photothermal transducers, owing to their capacity to efficiently produce heat in nanoscale volumes upon illumination at localized surface plasmon resonances (LSPR) tunable from ∼500 nm to over 2 μm based on their size and morphology. 24−26 This unique asset, named thermoplasmonics, 25,27−29 hails from the nanoparticles' large optical extinction cross section, defined here as the combination of both scattering and absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Other examples include the fabrication of light-responsive biomimetic soft robots for the transportation and manipulation of micro-objects, as well as the development of light-actuated in vitro cell culture platforms for precise manipulation and exertion of mechanical stimulations on living cells . However, a majority of the photoresponsive hydrogel actuators reported to date respond to near-infrared wavelengths, with only a few in the visible range, thus limiting the possibilities for multiwavelength actuation. , In this regard, gold nanoparticles are great candidates as photothermal transducers, owing to their capacity to efficiently produce heat in nanoscale volumes upon illumination at localized surface plasmon resonances (LSPR) tunable from ∼500 nm to over 2 μm based on their size and morphology. This unique asset, named thermoplasmonics, , hails from the nanoparticles’ large optical extinction cross section, defined here as the combination of both scattering and absorption. , Spherical gold nanoparticles smaller than 60 nm in diameter are not commonly used in soft actuation applications due to the weak temperature increase produced at the single-particle level. Nevertheless, in terms of photothermal efficiency, these nanoparticles exhibit excellent light-to-heat conversion properties because of the predominance of absorption over scattering on the overall extinction spectrum. Furthermore, such nanoparticles are easily synthesized using well-established protocols, which facilitates precise control over particle size and hence facile tunability of their optical properties in the visible range. In order to use these nanoparticles as nanoheaters in smart soft actuators, their collective photothermal behavior needs to be considered to avoid underestimating their potential heating capacity, , as it has been shown that illuminating a collection of nanoparticles can result in a temperature increase of several degrees with a uniform temperature profile, despite the nanometric size of the heat sources. , …”
Section: Introductionmentioning
confidence: 99%